The Utility of Verbal Therapy for Pediatric Cancer Patients and Survivors: Expressive Writing, Video Narratives, and Bibliotherapy Exercises - Jones, Jill K.; Evans, John F.; Barfield, Raymond C. (Frontiers in Pediatrics, 2021)
Childhood cancer is a stressful experience. No pediatric patient, however, should be made to feel as if their concerns and feelings about their cancer experience must be bottled up inside. Importantly, talking and writing about one’s illness has myriad implications for young cancer patients and survivors. The most salient of these may include increased understanding of one’s condition as well as improved physical and cognitive symptoms (e.g., lowered depression, decreased anxiety, and an enhanced quality of life overall). This literature review explores three promising avenues for verbal therapy in the pediatric oncology setting: expressive writing, video narratives, and bibliotherapy exercises. Several recent studies, covering verbal therapy methods from illness blogging to book interventions, are referenced and discussed. Ultimately, we conclude that expressive writing, video narratives, and bibliotherapy exercises are valuable, feasible, inexpensive, and acceptable tools for patients and survivors of childhood cancer to facilitate self-expression—and to find meaning in the uncertainty and anxiety that cancer inherently fosters. We recommend that future studies investigate this theme so that we may improve quality of life and mental health for pediatric cancer patients and survivors worldwide.